A Backstepping Control of Plant Protection Boom System Considering Input Constraints. (October 2020) - Li, Shujiang; Wu, Yue
Abstract: Aiming at the plant protection machine boom system with input constraints, uncertain disturbances and various nonlinear factors, a backstepping controller considering input saturation uncertain interference is proposed. The method introduces an auxiliary system, realizes the compensation of control saturation by designing new error variables, and solves the amplitude constraint problem of the control input. By constructing the appropriate Lyapunov function, the stability of the planter boom system is guaranteed. The simulation results show that the designed controller has good tracking performance and robustness.